Television of, by, and for the poor? on suffering and media ethics [review of] The Poverty of Television - Mangahas, Maria F. (2016)
Access online through this link: http://plarideljournal.org/article/television-poor-suffering-media-ethics
Keywords: Mass media ethics; Television programs; Poor people